PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN IPS PADA SISWA KELAS VIII DI UPTD SMP NEGERI 10 KUPANG - Aplonia Ernaningsih Hane Asan; Yeheskial Nggandung; Ari Data (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of learning motivation (Aspirations X1, Parental Support X2, Peers X3) on student learning outcomes. The background of this study is based on the low learning motivation of students indicated by the high number of incompleteness in the mid-semester summative. The research method used is a quantitative approach with data collection techniques through questionnaires, interviews, and documentation. The population in this study were all eighth grade students of UPTD SMP Negeri 10 Kupang, with a sample size of 60 respondents determined using purposive sampling techniques. Data analysis was carried out using the classical assumption test, multiple linear regression, t-test, f-test, and coefficient of determination test. The results of the study show that aspirations have a positive and significant impact on learning outcomes with a coefficient value of 5.304 and a significance of 0.000. Parental support has a positive and significant impact on learning outcomes with a coefficient value of 4.580 and a significance of 0.000. Peers also have a positive and significant impact on learning outcomes with a coefficient value of 3.563 and a significance of 0.000. Simultaneously, aspirations, parental support, and peer support had a positive and significant impact on learning outcomes, with a calculated F-value of 443.557 and a significance level of 0.000. Furthermore, the coefficient of determination test showed an R-squared value of 0.960, indicating that the three independent variables explained 96% of the influence of learning motivation on learning outcomes, with the remainder being influenced by other factors outside the study. Therefore, it can be concluded that learning motivation (aspirations, parental support, and peer support) is a crucial factor in improving student learning outcomes.